Brainstem neural mechanisms controlling locomotion with special reference to basal vertebrates - Lacroix-Ouellette, Philippe; Dubuc, Réjean (Frontiers in Neural Circuits, 2023)
Over the last 60 years, the basic neural circuitry responsible for the supraspinal control of locomotion has progressively been uncovered. Initially, significant progress was made in identifying the different supraspinal structures controlling locomotion in mammals as well as some of the underlying mechanisms. It became clear, however, that the complexity of the mammalian central nervous system (CNS) prevented researchers from characterizing the detailed cellular mechanisms involved and that animal models with a simpler nervous system were needed. Basal vertebrate species such as lampreys, xenopus embryos, and zebrafish became models of choice. More recently, optogenetic approaches have considerably revived interest in mammalian models. The mesencephalic locomotor region (MLR) is an important brainstem region known to control locomotion in all vertebrate species examined to date. It controls locomotion through intermediary cells in the hindbrain, the reticulospinal neurons (RSNs). The MLR comprises populations of cholinergic and glutamatergic neurons and their specific contribution to the control of locomotion is not fully resolved yet. Moreover, the downward projections from the MLR to RSNs is still not fully understood. Reporting on discoveries made in different animal models, this review article focuses on the MLR, its projections to RSNs, and the contribution of these neural elements to the control of locomotion. Excellent and detailed reviews on the brainstem control of locomotion have been recently published with emphasis on mammalian species. The present review article focuses on findings made in basal vertebrates such as the lamprey, to help direct new research in mammals, including humans.